The temperature-dependent duration of development and parasitism of three cereal aphid parasitoids, aphidius ervi, a-rhopalosiphi, and praon volucre - Sigsgaard, Lene (Wiley, 2000)
Temperature dependencies were established for the egg‐to‐mummy and mummy‐to‐adult phases, for mummy mortality, and for parasitism of Aphidius ervi Haliday, Aphidius rhopalosiphi De Stefani‐Perez, and Praon volucre (Haliday) (Hymenoptera, Aphidiidae), three parasitoids of Sitobion avenae (Fabricius) (Homoptera, Aphididae), at 8 °C, 12 °C, 16 °C, 20 °C, and 25 °C on winter wheat (cv. Haven). A physiological model described temperature‐dependent development over the full temperature range, whereas a linear model was fitted for data above 8 °C and used to estimate the lower temperature thresholds and day‐degrees (° D) required for development. The thresholds for A. ervi were 2.2 °C for egg‐mummy development and 6.6 °C for mummy‐adult development, those for A. rhopalosiphi were 4.5 °C and 7.2 °C, and those for P. volucre were 3.8 °C and 5.5 °C. The time to develop into mummies and adults differed significantly between the three species: A. ervi development into mummies required an average of 159 ° D, while development into adults took an average of 73 ° D. The corresponding average times required for A. rhopalosiphi and P. volucre to develop mummies were 124° D and 126° D, while their development into adults required an average of 70° D and 150° D, respectively. Mummy mortality was 25–35% at 8 °C and less at the higher temperatures tested, but began to increase again at 25 °C, showing a quadratic relationship between mortality and temperature. Parasitization was very low or, in the case of P. volucre, absent up to 12 °C and thereafter increased with increasing temperature. The relationship between parasitization, recorded as percent aphids mummified, and temperature was linear at the temperatures tested and depended on species. A. ervi superparasitized 11.1% aphids at 20 °C and 16.6% aphids at 25 °C, whereas superparasitism was low in A. rhopalosiphi and absent in P. volucre. From 16 °C to 25 °C the P. volucre sex ratio increased. For A. ervi and A. rhopalosiphi there was no trend with temperature, but at 20 °C and 25 °C it was close to even. Field data for 1996 and 1997 allowed for a comparison of actual and expected emergence of overwintering mummies. In both years, parasitoids were predicted to have emerged from overwintering mummies well in advance of the onset of aphid infestation, and more than a month earlier than the first parasitized aphids were found in winter wheat. Observations from trap plants in other crops supported the predictions of the models. Other factors that can affect biological control by cereal aphid parasitoids are discussed.